Cost-effectiveness of janus kinase inhibitors for rheumatoid arthritis: A systematic review and meta-analysis of cost-utility studies - Kumar, S. Sajith; Haridoss, Madhumitha; Venkataraman, Krishnamurthy; Bagepally, Bhavani Shankara (Frontiers in Pharmacology, 2022)
Introduction: Janus kinase inhibitors (JAK-i), a class of targeted synthetic disease-modifying antirheumatic drugs (tDMARDs), are suggested as second or third-line therapies in rheumatoid arthritis (RA). Synthesized cost-effective evidence would aid in informed decision-making given the similar clinical effectiveness of JAKi, but incongruent cost-effectiveness reports. Methods: Literature search was conducted in PubMed, Embase, Scopus, and Tufts Medical Centers’ cost-effective analysis registry. We pooled the incremental net benefit (INB) with 95% confidence interval (CI) using random-effects model and the heterogeneity was assessed using Cochrane-Q test and I2 statistic. Modified economic evaluation bias checklist was used to assess the quality of selected studies. Publication bias was assessed using a funnel plot and Egger’s test. The Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) assessment was performed to assess the certainty of outcomes presented. Results: We included seventeen relevant studies for systematic review, of which fifteen were eligible for meta-analysis. The meta-analysis results showed that JAK-i is cost-effective compared to csDMARDS/bDMARDs with a pooled INB (INBp) of $19,886 (95% CI, 1,635 to 38,137) but with considerable heterogeneity (I2 = 99.14). As a second-line treatment for csDMARD failed RA, JAK-i is cost-effective than csDMARD/bDMARD with a pooled INB of $23,144 (74.1–46,214) and high heterogeneity (I2 = 99.67). But on a separate analysis JAK-i as second-line treatment is not cost-effective than TNF-a-i (INBp = $25,813, -5,714 to 57,340). However, leave-one-out analysis found that omitting a single outlier makes JAK-i cost-effective. Further, JAK-i is not cost-effective as a third-line treatment for csDMARD-TNF-a-I failed RA, compared to csDMARDs/bDMARDs with INBp $26,157 (-7,284 to 59,598). Conclusion: Meta-analysis suggests that JAK-i is cost-effective when used after csDMARD failure but not cost-effective when used after csDMARD-TNF-a-i failure with low certainty of evidence. Clinical Trial Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021222541, identifier CRD42021222541